The Papers of Jefferson Davis : July 1846-December 1848 - Davis, Jefferson, 1808-1889 (Book collections on Project MUSE., 1981)
Lynda L. Crist, Associate EditorMary S. Dix, Assistant EditorAt the end of Volume 2 Jefferson Davis had left Congress to become a colonel in the First Mississippi Regiment. The first item in this volume is a speech as he prepares to leave on a riverboat to serve in the Mexican War. The years 1846 through 1848 see Davis play a conspicuous role in the war and in the subsequent political clashes and controversies over slavery. Volume 3 details Davis' first experience in battle as an officer of a regiment as well as his initial term as a U.S. senator. He received both praise and critic.